2017
DOI: 10.4236/ojst.2017.74016
|View full text |Cite
|
Sign up to set email alerts
|

Dental Aesthetics: A Study Comparing Patients’ Own Opinions with Those of Dentists

Abstract: Objective: A beautiful smile is perceived as important but the components that contribute to the patient's concept of a beautiful smile have not been fully investigated. Hence this study aimed to compare the views of patients on their own dental aesthetics with those of a group of dentists. It also assessed the patients' willingness to undergo aesthetic treatment. Methods: Fifty patients, who ranged in age from 24 to 76 years, completed self-assessment questionnaires. Photographs were taken of these patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The aesthetic importance of the smile has been extensively discussed in the literature. 2,[17][18][19] Orthodontics, a dental specialty that works directly with smile aesthetics, requires continuous updating of its material collection to keep up with the demands of the overall population. 4,5,[20][21][22][23][24] Therefore, testing the color change of elastomeric ligatures is required to guide orthodontists seeking to respect the decision of patients desiring an aesthetic smile even during orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aesthetic importance of the smile has been extensively discussed in the literature. 2,[17][18][19] Orthodontics, a dental specialty that works directly with smile aesthetics, requires continuous updating of its material collection to keep up with the demands of the overall population. 4,5,[20][21][22][23][24] Therefore, testing the color change of elastomeric ligatures is required to guide orthodontists seeking to respect the decision of patients desiring an aesthetic smile even during orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The aesthetic importance of the smile has been extensively discussed in the literature. 2 , 17 - 19 Orthodontics, a dental specialty that works directly with smile aesthetics, requires continuous updating of its material collection to keep up with the demands of the overall population. 4 , 5 , 20 - 24 …”
Section: Discussionmentioning
confidence: 99%
“…In the specialised literature there are concrete information about the realization of aesthetic dental treatment such as: measurements, angles, electronic systems for previewing the future appearance, systems used in collaboration with the laboratory of dental technique (digital fingerprint of the oral cavity, CAD / CAM). There are, also, many evasive information about issues such as the exposure of various artworks to understanding the phenomena of contrast, luminosity, shadows, symmetry (Demir, Oktay, & Topcu, 2017;Yu, Cheng, Zhou, & Cheng, 2017), (Moon & Millar, 2017). Our study enters this new direction of investigation.…”
Section: Introductionmentioning
confidence: 87%
“…Further analysis of the cost attribute revealed that willingness-to-pay per participants decreases with increasing age. Reduced incomes at an older age (e.g., pension), expensive treatments, or a reduced awareness of aesthetically high-quality as well as prioritization of functionality could be a reason [69][70][71]. Presumably, the older the patient, the more intentional the dentist is in communicating that a dental crown is possibly the last and only alternative for tooth preservation [72].…”
Section: Plos Onementioning
confidence: 99%